2014
DOI: 10.1111/clr.12327
|View full text |Cite
|
Sign up to set email alerts
|

In‐vitro evaluation of the tolerance of surgical instruments in templates for computer‐assisted guided implantology produced by 3‐D printing

Abstract: OBJECTIVE: The aim of this in-vitro study was to compare the tolerance of surgical instruments in surgical guides produced by 3-D printing, without metal sleeves to a surgical guide with conventional metal sleeves from two different manufacturers. MATERIALS AND METHODS: Lateral movements of drill tips caused by tolerance between the sleeve and drill key and between the drill key and the drill were recorded after application of a standardized force to the surgical instruments. Four groups were tested: Control 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 10 publications
2
56
0
Order By: Relevance
“…Surgical templates without metallic sleeves can be easily designed and customized using dedicated software. This allows us to eliminate the metal tubes, and possibility to reduce the tolerance between the printed sleeves and the drill-guiding keys [13]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical templates without metallic sleeves can be easily designed and customized using dedicated software. This allows us to eliminate the metal tubes, and possibility to reduce the tolerance between the printed sleeves and the drill-guiding keys [13]. …”
Section: Discussionmentioning
confidence: 99%
“…This protocol includes CAD and the use of 3D printing for surgical guide production without the use of any metal sleeves and with a more intimate contact between the guide and the drill-guiding drill key [13]. …”
Section: Discussionmentioning
confidence: 99%
“…The findings are consistent with long established engineering principles that an increase in drilling length is associated with an increase in lateral vibration and chattering. As an example, in a previous study Schneider et al demonstrated that drill lateral movement, resulting from tolerance of surgical instruments can be reduced by decreasing the drill length and increasing the key height above the sleeve. Whether this surgical tolerance and lateral movement would translate into a significant deviation in a clinical scenario has not been established.…”
Section: Discussionmentioning
confidence: 99%
“…As the popularity of the sCAIS increases, the responsible introduction of it's broad application requires a knowledge of common variables and decision‐making points during treatment planning and execution. Errors during data acquisition, data transfer, data processing, treatment planning, guide design and production, as well as surgical execution might all contribute to increased deviations from the virtually planned implant position . The variables encountered during the treatment‐planning step by itself are numerous.…”
Section: Introductionmentioning
confidence: 99%
“…(2) Incorrect fit of the surgical template on the remaining teeth or surgical transfer: The correct fit may be guaranteed by choosing a small offset‐spacer in the stereolithographic production process and continuous surveillance during surgery. Perfect adaption of the planned implant and the corresponding sleeve, burr, drill handle, drill cylinder, and other material is recommended to minimize errors during the surgical phase …”
Section: Discussionmentioning
confidence: 99%